Strategi Pemberdayaan Lembaga Perekonomian Umat - Ratno Agriyanto (IAIN Ponorogo, 2012)
Cooperative boarding school in Semarang as a local institution and the people show less than optimal performance when compared with other conventional cooperatives. Therefore, the researchers offer a model of cooperative empowerment boarding school with a balanced scorecard approach has been adapted to the characteristics of cooperative boarding school, in order to improve performance. The study was conducted on 11 cooperative boarding an active status, the unit being analyzed is the manager, and board members. Using descriptive analysis techniques with a qualitative approach. The research, among others, found to modify the scorecard on each perspective according to the characteristics inherent in the cooperative boarding school. The results of the cooperative implementation of balanced scorecard on the boarding school showed quite good performance in this category. Cooperative strategy of empowering Islamic boarding schools can not be compared among cooperative boarding school but must be done by increasing the scorecard perspectives that have poor performance.